1986
DOI: 10.1113/jphysiol.1986.sp016304
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic slow excitation and muscarinic inhibition of synaptic transmission in the rat neostriatum.

Abstract: SUMMARY1. Intracellular recording from neurones in rat neostriatal slices was used to compare the muscarinic effects of endogenous acetylcholine (ACh) released from cholinergic neostriatal synapses with the action of exogenously applied muscarinic agonists.2. Repetitive electrical stimulation in the neostriatum evoked a series of fast excitatory post-synaptic potentials (e.p.s.p.s) followed by a short, variable period of input resistance decrease. In the presence of the acetylcholinesterase (AChE) inhibitor, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
34
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 36 publications
(56 reference statements)
4
34
0
Order By: Relevance
“…In a substantial number of non-histamine-responding neurones, however, ACh induced a net inward current, possibly resulting from the reduction of IM. This is consistent with the report that ACh reduces a voltage-dependent K+ conductance that is identical to IM in principal neurones (Dodt & Misgeld, 1986). Therefore, the reduction of K+ current might be elicited in large aspiny neurones which serve as cholinergic interneurones.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In a substantial number of non-histamine-responding neurones, however, ACh induced a net inward current, possibly resulting from the reduction of IM. This is consistent with the report that ACh reduces a voltage-dependent K+ conductance that is identical to IM in principal neurones (Dodt & Misgeld, 1986). Therefore, the reduction of K+ current might be elicited in large aspiny neurones which serve as cholinergic interneurones.…”
Section: Discussionsupporting
confidence: 92%
“…Most interneurones are known to be cholinergic and project to principal neurones in the neostriatum. Endogenous and exogenous ACh modifies the activities of rat neostriatal neurones through the reduction of K+ conductance (Dodt & Misgeld, 1986), which has been partly shown in the present study. Moreover, a voltage-dependent transient K+ conductance in cultured neurones of the rat neostriatum is also affected by ACh (Akins, Surmeier & Kitai, 1990).…”
supporting
confidence: 73%
“…2A and B, right panels) but not by hexamethonium (10-50 /LM, n = 8). In addition, both actions of carbachol were mimicked by superfusion of muscarine (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) JtM, n = 8), oxotremorine (1 JtM, n = 3) and oxotremorine-M (1 /,M, n = 8), but not by the nicotinic agonist DMPP (10 /IM, n = 5), consistent with their mediation via a muscarinic receptor. Previous studies have suggested that the M1 receptor is involved in the muscarinic reduction of the AHP in hippocampal pyramidal cells (Dutar & Nicoll, 1988) and myenteric plexus neurons (Galligan, North & Tokimasa, 1989).…”
Section: S Washburn and H C Moisesmentioning
confidence: 99%
“…In the case of the amygdala, selective inhibition of these neurons could be helpful in certain epilepsies; the amygdala is among the most readily kindled of brain regions, and this is blocked by muscarinic antagonists (27,28). Conversely, selective agonists at M1 receptors would be expected to excite the principal cells of these regions by direct excitation (11,29) and by reduction of GABA-mediated feedback inhibition, while having no effect on the excitatory drive to the cells mediated by glutamate. The cholinergic innervation of the amygdala from the nucleus basalis is one site of the typical neurodegenerative changes associated with Alzheimer disease (1,30), and the present findings therefore point to the possible value of M1 agonists and M3 antagonists in this disease.…”
mentioning
confidence: 99%